2008
DOI: 10.1073/pnas.0800237105
|View full text |Cite|
|
Sign up to set email alerts
|

Salt tolerance of Arabidopsis thaliana requires maturation of N -glycosylated proteins in the Golgi apparatus

Abstract: Protein N -glycosylation in the endoplasmic reticulum (ER) and in the Golgi apparatus is an essential process in eukaryotic cells. Although the N -glycosylation pathway in the ER has been shown to regulate protein quality control, salt tolerance, and cellulose biosynthesis in plants, no biological roles have been linked functionally to N -glycan modifications that occur in the Golgi apparatus. Herein, we provide evidence that mutants defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
257
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 221 publications
(273 citation statements)
references
References 50 publications
13
257
0
1
Order By: Relevance
“…Importance of functional cellulose biosynthesis for salt tolerance was further supported by the novel finding of increased salt-sensitivity of rsw2-1 and rsw1-1 single mutants. 1 Our previous and current data have implications that affect our view of protein N-glycosylation in plants. First, after all, plant complex N-glycans confer important in vivo functions to secreted/ secretory glycoproteins, i.e., protect root growth from salt/osmotic stress.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Importance of functional cellulose biosynthesis for salt tolerance was further supported by the novel finding of increased salt-sensitivity of rsw2-1 and rsw1-1 single mutants. 1 Our previous and current data have implications that affect our view of protein N-glycosylation in plants. First, after all, plant complex N-glycans confer important in vivo functions to secreted/ secretory glycoproteins, i.e., protect root growth from salt/osmotic stress.…”
mentioning
confidence: 98%
“…This showed that cgl1 and stt3a enhance cellulose deficiency of rsw2-1, and in turn indicate that the KOR1/RSW2 protein requires complex N-glycans for its function in vivo. Further pyramiding of these mutations resulted in incremental enhancement of growth defects as well as developmental defects of the host plants (Kang et al, (2008), and Fig. 1).…”
mentioning
confidence: 99%
See 3 more Smart Citations